Estimation of free fatty acid content in oils, fats, and biodiesel by (1)H NMR spectroscopy - Satyarthi, Jitendra K.; Srinivas, D.; Ratnasamy, Paul (Energy & Fuels, 2009)
A novel (1)H NMR method for the quantification of free fatty acid (FFA) content in vegetable oils, animal fats, and biodiesel is reported. Nonedible oils and animal fats, which are increasingly being explored as cheaper, renewable feed stocks for biodiesel production by transesterification with methanol, contain a significant amount of FFA along with other acidic impurities. The (1)H NMR spectroscopic method is found to be more accurate than the conventional titrimetric analysis for the estimation of FFA content especially in those cases where acidic entities other than the FFA are also present in the feedstock. The titrimetric methods provide a gross acid value which corresponds to that of FFA and other acidic impurities. Our NMR method provides the FFA content exclusively. In the case of refined edible oils (wherein the other acidic impurities are negligible), the results obtained from the (1)H NMR method are comparable with those from the titrimetic analysis.